2005
DOI: 10.1590/s0100-46702005000300007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical evidence of sulfinic acid derivative as an intermediate in the reduction of aromatic sulfonyl chloride in an aprotic medium

Abstract: The electrochemical reduction of p-nitrobenzenesulfonyl chloride (NBSCl) in dimethylsulfoxide (DMSO) solution is used here as a model to investigate the role of sulfinic acid derivative in this compound's global reduction process. Cyclic voltammetric experiments reveal the production of sulfinic acid derivative, which is important in chemical reactions involving the original compound and other intermediates. This paper also discusses the probable mechanisms of the reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The thiosulfonates are usual products in the reduction of these compounds and have been shown to result from chemical reactions in solution and are not formed at the electrode through direct reduction of the parent molecules. [59][60][61][62] An important result here is that the disulfides result from the reduction of the thiosulfonates as we have demonstrated through electrolysis of the phenylthiophenylsulfonate 2c (see ESIw). The reduction peak of this compound is located at a potential very close to that of the parent sulfonyl chloride (see ESIw) and hence is reduced during the electrolysis, which is set at the reduction potential of the latter compound.…”
Section: Electrolysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The thiosulfonates are usual products in the reduction of these compounds and have been shown to result from chemical reactions in solution and are not formed at the electrode through direct reduction of the parent molecules. [59][60][61][62] An important result here is that the disulfides result from the reduction of the thiosulfonates as we have demonstrated through electrolysis of the phenylthiophenylsulfonate 2c (see ESIw). The reduction peak of this compound is located at a potential very close to that of the parent sulfonyl chloride (see ESIw) and hence is reduced during the electrolysis, which is set at the reduction potential of the latter compound.…”
Section: Electrolysesmentioning
confidence: 99%
“…A number of electrochemical investigations have been reported in different media but a clear picture of the details of the reduction mechanism is still lacking. [59][60][61][62] The studies have shown different results in terms of involved mechanisms, number of consumed electrons, and yielded different products. [59][60][61][62] A more rigorous study would certainly help to understand the reduction mechanism and rationalize the observed differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…−1.5 V, giving carboxylate anions that can rearrange and form a series of different products 42 and (iii) at more cathodic potential (above −2.0 V), the sulfonyl chloride S−Cl or the sulfonamide S−N bond cleavage. 43,44 In the anodic region, the cyclic voltammograms revealed an irreversible peak at 0.706 V for the dansyl . Silva et al 1811 Vol.…”
Section: Electrochemical Characterization Of Dansyl Derivatives and Ementioning
confidence: 99%
“…−1.5 V, giving carboxylate anions that can rearrange and form a series of different products 42 and (iii) at more cathodic potential (above −2.0 V), the sulfonyl chloride S−Cl or the sulfonamide S−N bond cleavage. 43,44 In the anodic region, the cyclic voltammograms revealed an irreversible peak at 0.706 V for the dansyl Silva (Figure 3). These peaks were attributed to the tertiary amine oxidation of both derivatives, suggesting a fast following coupled chemical reaction and/or an irreversible charge transfer reaction, but with no significant changes observed at the electrode surface.…”
Section: Electrochemical Characterization Of Dansyl Derivatives and Ementioning
confidence: 99%